Analisis Strategi Pemasaran Untuk Meningkatkan Volume Penjualan Bumbu UD. Nurhalimah Pasar Ujung Batu Kecamatan Sosa Kabupaten Padang Lawas Sumatera Utara Dalam Kajian Ekonomi Islam - Nazla Daulay; Sri Ramadhani; Nuri Aslami (Universitas Labuhanbatu, 2023)
This study aims to analyze marketing strategies to increase sales Volume of UD Nurhalimah Ujung Batu market, Sosa District, Padang Lawas regency, North Sumatra in Islamic Economic Studies with SWOT analysis . This research is a field study using qualitative descriptive methods; primary and secondary data sources are used, and data collection procedures include interviews, observations, and documentation. Subjects in this study are owners ,employees, consumers and society. The focus of this study is how the application of marketing strategy management to increase sales volume at UD Nurhalimah with SWOT analysis the results of this study indicate that implementing a marketing mix strategy or often referred to as the marketing mix, namely: Product Marketing Strategy, price Marketing Strategy, place marketing strategy, promotional marketing strategy. Sourced from the SWOT analysis of UD Nurhalimah seasoning shows that it is located in an aggressive or growing position in the strategy (SO). Where in this position has a solid position and describes the external opportunities that exist and avoid the influence of negative potential threats.